Emergency mental health care for chi?ldren and adolescents outside of regular working hours: 7 years outcomes from a tertiary hospital - PERDAHLI FİŞ, NEŞE; AY, NADİYE PINAR (My University, 2022)
Objective: This study aims to define the clinical characteristics and management strategies of children and adolescents presenting with psychiatric crises to the emergency department (ED) of a tertiary health care facility outside of working hours, and to identify predictors of multiple ED visits among them.Methods: From January 2012 to December 2018, retrospective records of patients presenting with psychiatric symptoms to the ED and examined by a child psychiatrist after 5 p.m. on weekdays and for 24 h on weekends and public holidays were analyzed.Results: Our sample consisted of 1576 visits and 1364 patient (Female:Male=1.8:1, mean age=14.86 +/- 2.72). The most common reason for visits was self-injurious thought or behaviors (SITB), and the most common diagnosis was depression. While depression was statistically more common in girls, attention deficit hyperactivity disorder, autism and/or intellectual disability (ASD/ID), psychotic disorders, and bipolar disorder were more common in boys. The forensic evaluation was the most common reason for visits among children younger than 6 years old. Of visits, 23% transferred to hospitalization. A history of mental health contact was the lowest in depression (37.5%), psychosis (34.1%), and substance use disorders (33%). Of patients, 10.8% had multiple visits. A history of mental health contacts, conduct disorder, ASD/ID, bipolar disorder, psychotic disorder, and dissociative disorder were predictors of multiple visits to ED with psychiatric reasons.Conclusion: Emergency mental health care outside of regular working hours can be a critical step in the diagnosis and treatment of serious psychiatric disorders in children and adolescents.
Keywords: Sağlık Bilimleri; Health Sciences; Psikiyatri; Klinik Tıp (MED); PSYCHIATRY; Clinical Medicine (MED); Psikiyatrik Ruh Sağlığı; Psikiyatri ve Ruh Sağlığı; Psychiatric Mental Health; Psychiatry and Mental Health; Adolescents; Depression; Emergency; Mental health; Psychiatry; METAANALYSIS; DISORDERS; SERVICES; Adolescents; Depression; Emergency; Mental health; Psychiatry